2002
DOI: 10.1084/jem.20020072
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunization Against the Vascular Endothelial Growth Factor Receptor flk1 Inhibits Tumor Angiogenesis and Metastasis

Abstract: The vascular endothelial growth factor (VEGF) receptor fetal liver kinase 1 (flk1; VEGFR-2, KDR) is an endothelial cell–specific receptor tyrosine kinase that mediates physiological and pathological angiogenesis. We hypothesized that an active immunotherapy approach targeting flk1 may inhibit tumor angiogenesis and metastasis. To test this hypothesis, we first evaluated whether immune responses to flk1 could be elicited in mice by immunization with dendritic cells pulsed with a soluble flk1 protein (DC-flk1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 34 publications
4
117
1
1
Order By: Relevance
“…[8][9][10] Other endothelial membrane proteins involved in angiogenesis such as integrin b3, Tie-2, endoglin and fibroblast growth factor receptor-1 (FGFR-1) have been under preclinical studies and shown therapeutic potential in cancer treatment. 11 Dendritic cells pulsed with angiogenesis-associated antigens [12][13][14][15] and endothelial-dendritic cell hybrids 16 have also proved effective in angiogenesis inhibition. Because of the fact that angiogenic endothelial antigens remain largely unrevealed, fixed human umbilical vascular endothelial cells (HUVECs), 17 murine hepatic sinusoidal endothelial cells 18 or viable HUVECs 19 were used as vaccines to elicit autoimmunity that attacked tumor endothelium and hence inhibited tumor growth.…”
mentioning
confidence: 99%
“…[8][9][10] Other endothelial membrane proteins involved in angiogenesis such as integrin b3, Tie-2, endoglin and fibroblast growth factor receptor-1 (FGFR-1) have been under preclinical studies and shown therapeutic potential in cancer treatment. 11 Dendritic cells pulsed with angiogenesis-associated antigens [12][13][14][15] and endothelial-dendritic cell hybrids 16 have also proved effective in angiogenesis inhibition. Because of the fact that angiogenic endothelial antigens remain largely unrevealed, fixed human umbilical vascular endothelial cells (HUVECs), 17 murine hepatic sinusoidal endothelial cells 18 or viable HUVECs 19 were used as vaccines to elicit autoimmunity that attacked tumor endothelium and hence inhibited tumor growth.…”
mentioning
confidence: 99%
“…20) In this work, however, the involvement of cellular immunity in the antitumor effect was not determined. More recently, dendritic cells pulsed with flk-1 (murine VEGFR-II) 21) as well as a DNA vaccine of flk-1 22) have been shown to induce CTLs with lytic activity against endothelial cells, leading to inhibition of tumor growth in mice. The efficacy of our vaccines was comparable with the reported data, not only in in vitro CTL assays, but also in in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…There is certainly a possibility that antiangiogenesis can cause spontaneous bleeding under specific experimental conditions, 7,21) as well as interfering with physiologic angiogenesis, impairing wound healing 22) or pregnancy. 21) On the other hand, however, most authors have reported only mild or no side effects during longterm follow-up of treated animals. 6-8, 11, 21-27) In this study, we found no evidence of complications due to endothelial vaccination in mice, but further studies on the safety of endothelial vaccines, as well as other antiangiogenic therapeutics, are needed.…”
Section: )mentioning
confidence: 99%
“…Although recently most preclinical studies have focused on the induction of T-cell responses to VEGFR-2 as a means to target tumour angiogenesis, 17,18,20,21,34,35 antibody-based therapies have proved to be clinically effective for the treatment of metastatic cancer. Bevacizumab (Avastin) is a monoclonal antibody specific for VEGF and has recently been approved by the FDA for treatment of patients with metastatic colorectal cancer.…”
Section: Inhibition Of Angiogenesis By a Sfv Vector Expressing Vegfr-mentioning
confidence: 99%
“…One of the most successful of these Bevacizumab (Avastin, Genentech, San Francisco, CA, USA) has shown improved survival of patients with metastatic colorectal cancer in a phase III study. 15 Recently, several preclinical studies have shown that active immunization with purified xenogenic VEGFR-2, 16 dendritic cells (DC) pulsed with autologous VEGFR-2 protein/peptides, 17,18 DC transfected with VEGFR-2 mRNA 19 or vaccination with attenuated Salmonella typhimurium carrying VEGFR-2 cDNA 20,21 can break immunological tolerance to VEGFR-2 leading to inhibition of tumour growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%